Rows of squares: A standard model for transcribing traditional African music in Cameroon - Ngumu, Pie-Claude; Tracey, Andrew (International Library of African Music, 1980)
Transcribing traditional African music is an arduous undertaking. On the one hand the musicians, composers of the music, stem from a long line of generations whose only way of passing their art to posterity was by word of mouth. They had no technique of preserving their art in writing. On the other hand, these oral traditions have been subject, for unforeseeable ecological reasons, to the often unpleasant after-effects of pollution, which, instead of helping them to develop greater vitality, often deal the final blow which leads to their disappearance. Yet these musics, as products of man’s artistic and spiritual progress, embody messages of wisdom directed at all generations of our humankind. As such they convey not only well- crafted material forms capable of affecting our deepest feelings, but also modes of thought which can richly nourish and dynamically stimulate our creativity. It is in this sense that these musical traditions are worthy of interest and deserve our close attention.
Keywords: African Music; Cameroon